Hibridizacija slovaščine v rabi kot rezultat konvergence sodobne slovaščine s češčino - Pallay, Jozef (Jezik in slovstvo, 2025)
In this paper we outline the main historical development trends of Slovak in relation to the divergence and convergence with Czech, which is closely related to the issue of linguistic purism. The focus of this outline is based on a brief overview of the most recent state of this development after the dissolution of Czechoslovakia and the emergence of Slovakia as a sovereign state. Despite the new situation and the expectations of divergence, with a gradual distancing of the two languages, our observations suggest that in actual use – and as a result of the asymmetry of the mutual influences of Slovak and Czech in the economic, educational and especially media spheres – Slovak is paradoxically converging with Czech, although partly as a result of interference based on obvious linguistic errors. Using a few examples from contemporary live communication, as a result of empirical observation and partly from internet discussions of prominent Slovak print media, we try to show the untransparent process of hybridisation of Slovak with Czech at the sound, vocabulary, word-formation, lexical and semantic and stylistic levels.
Keywords: Czech; Czech and Slovak language in contact; češčina; češčina in slovaščina v stiku; dvojezikovnost; hibridizacija; jezikovna divergenca; jezikovna konvergenca; linguistic convergence; linguistic divergence; linguistic hybridisation; purism; purizem; Slovak; slovaščina; transfer